1995
DOI: 10.1073/pnas.92.26.12085
|View full text |Cite
|
Sign up to set email alerts
|

Liver colonization competence governs colon cancer metastasis.

Abstract: Tumors that metastasize do so to preferred target organs. To explain this apparent specificity, Paget, > 100 years ago, formulated his seed and soil hypothesis; i.e., the cells from a given tumor would "seed" only favorable "soil" offered by certain organs. The hypothesis implies that cancer cells must find a suitable "soil" in a target organ-i.e., one that supports colonization-for metastasis to occur. We demonstrate in this report that ability of human colon cancer cells to colonize liver tissue governs whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 24 publications
3
46
1
Order By: Relevance
“…Scale bars=100um and its potential of metastasis. The findings of our study conform to the related reports of previous studies (Fidler 1991;Kuo et al, 1995). In the experiment we found the liver metastatic rate of the orthotopic model was even higher than that of clinical gallbladder carcinoma, which may be due to the cases that we chose.…”
Section: Discussionsupporting
confidence: 82%
“…Scale bars=100um and its potential of metastasis. The findings of our study conform to the related reports of previous studies (Fidler 1991;Kuo et al, 1995). In the experiment we found the liver metastatic rate of the orthotopic model was even higher than that of clinical gallbladder carcinoma, which may be due to the cases that we chose.…”
Section: Discussionsupporting
confidence: 82%
“…The ''seed and soil'' hypothesis of Paget (1) assumes direct interaction of tumors and normal cells (i.e., ''the seeds growing in the soil''), the analogy of tumor cells growing in a distant organ. This hypothesis was confirmed by us in 1995 when we showed that colon tumors would metastasize to the liver only if the tumor tissue were able to grow when implanted directly on the liver (13). If colon tumor tissues were unable to grow when implanted directly on the liver, the tumors were also unable to metastasize.…”
Section: Discussionsupporting
confidence: 65%
“…Matrigel, an extracellular matrix that contains several growth factors and cytokines, was used as a ''burst-supporting'' agent in the present study, although coculture with various growth factors, cytokines, extracellular matrix components, and fibroblasts might also augment cell proliferation and capsule burst. Regarding the second condition, some cancer cells have never been reported to proliferate in liver even after direct intrahepatic injection, indicating that the liver is not an appropriate soil for some cell lines (18,50). Application of the present microcapsule system to those cell lines might not generate liver metastases, even if they have the capacity to rupture the outer layer of microcapsules.…”
Section: Liver Metastases Model By Encapsulated Cancer Cellsmentioning
confidence: 99%
“…Alternative strategies for obtaining liver metastases with cancer cells of low metastatic potential include orthotopic implantation, by injecting cancer cell suspensions, or by surgical transplantation of tumor fragments (13)(14)(15). Obstacles in the latter strategy include the presence of undesired metastases and are moreover difficult to reproduce in terms of the frequency and extent of metastases (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%